Pengaruh Komorbid dan Jenis Terapi terhadap Outcome Kolesterol Total Pasien Dislipidemia - Fitri Apriliany; Zullies Ikawati; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Dislipidemia is one of the main risk factors of cardiovascular diseases that contributed more than 25% of death in this world. Hypertension and DM are associated with comorbidity in chronic disease, include of dislipidemia. This study aimed to determine the effect of comorbid and type of therapy on clinical outcomes in the outpatient installation at Puskesmas Jetis, Yogyakarta. This research is descriptive observational analytic with a cross-sectional. Data derived from primary data and secondary data. The inclusion criteria were patients dyslipidemia, received antidyslipidemia at least 3 months before the study, completed medical record, willing to able respondents, and can communicate well. Those who were pregnant or breastfeeding were excluded from the study. Data analysis used the Wilcoxon test. Most of respondents were majority dominated by women (86,14%), hypertension is the most comorbid (42,46%), most of patients used simvastatin (76,24%), gemfibrozil (16,83%), and combination of simvastatin+gemfibrozil (6,93%). The analysis showed that there was a significant effect on patients with comorbid diabetes and used simvastatin value before and after therapy for 3 months (p<0,05). This result showed that there was an effect of diabetes comorbidities and simvastatin therapy on the total cholesterol of patients, So this study implies that in providing statin therapy need to consider comorbid because they will affect to total cholesterol which one comorbid management that good need to achieve optimal therapeutic and type of therapy must be correct to improve outcome.